Experience of taking care of children exposed to HIV: a trajectory of expectations - Willyane de Andrade Alvarenga; Giselle Dupas (Universidade de São Paulo, 2014)
OBJECTIVE: to learn about the experience of caregivers/mothers providing care to infants exposed to HIV through vertical transmission.METHODS: this qualitative study used Symbolic Interactionism as the theoretical framework. A total of 39 caregivers of children exposed to HIV in follow-up at a specialized service were interviewed. Data were analyzed through inductive content analysis.RESULTS: four categories were identified that report on the lonely experience of handling the child's antiretroviral therapy, mainly due to a lack of information or incomplete information; being attentive to required care, such as the use of prophylaxis for pneumonia, vaccines, and other practices restricted to the mother-child interaction; the desire to omit the HIV out of fear of prejudice and fear of the disease, considering future prospects.CONCLUSION: the HIV and the threat this infection may affect the child cause apprehension and feelings such as fear, guilt and anxiety in the caregivers. Healthcare workers need to work together with mothers so they are able to cope with demands and distress. Only then will the treatment to avoid vertical transmission be efficient and will mother and child be supported during the process, despite apprehension with the outcome.